Quantifying the impact of the Public Health Responsibility Deal on salt intake, cardiovascular disease and gastric cancer burdens: interrupted time series and microsimulation study - Laverty,AA; Kypridemos,C; Seferidi,P; Vamos,EP; Pearson-Stuttard,J; Collins,B; Capewell,S; Mwatsama,M; Cairney,P; Fleming,K; O'Flaherty,M; Millett,C (Journal of Epidemiology and Community Health, 2019)
Background In 2011, England introduced the PublicHealth Responsibility Deal (RD), a public-privatepartnership (PPP) which gave greater freedom to thefood industry to set and monitor targets for salt intakes.We estimated the impact of the RD on trends in saltintake and associated changes in cardiovascular disease(CVD) and gastric cancer (GCa) incidence, mortality andeconomic costs in England from 2011–2025.Methods We used interrupted time series modelswith 24 hours’ urine sample data and the IMPACTNCDmicrosimulation model to estimate impacts of changes insalt consumption on CVD and GCa incidence, mortalityand economic impacts, as well as equity impacts.Results Between 2003 and 2010 mean salt intake wasfalling annually by 0.20 grams/day among men and 0.12g/d among women (P-value for trend both < 0.001).After RD implementation in 2011, annual declines insalt intake slowed statistically significantly to 0.11 g/damong men and 0.07 g/d among women (P-values fordifferences in trend both P < 0.001). We estimated thatthe RD has been responsible for approximately 9900(interquartile quartile range (IQR): 6700 to 13,000)additional cases of CVD and 1500 (IQR: 510 to 2300)additional cases of GCa between 2011 and 2018. Ifthe RD continues unchanged between 2019 and 2025,approximately 26 000 (IQR: 20 000 to 31,000) additionalcases of CVD and 3800 (IQR: 2200 to 5300) cases ofGCa may occur.Interpretation Public-private partnerships such as theRD which lack robust and independent target setting,monitoring and enforcement are unlikely to produceoptimal health gains.